The Improvement of Teachers’ Professional Competency Through Hots-Based Training - Astutik, Kurnia Fuji; Roesminingsih, Erny (JPI (Jurnal Pendidikan Indonesia), 2021)
This study aims to analyze the difference in the average learning outcomes between pre-test and post-test, analyze the effect of HOTS training on teacher professional competence. This research method is quasi-experimental using a quantitative approach. The research sample was 35 elementary school teachers. Data collection in this study using the test method. The design used was one group pre-test post-test design which was analyzed using paired t-test. Hypothesis test results show that there is a difference in the average learning outcomes between the pre-test and post-test, there is a significant effect of HOTS training on the professional competence of teachers. There are still many variables that can be explored to further optimize the formation of policy framework models and theoretical frameworks to improve teacher professional competence.